Determinants of Commercial Bank Performance and Its Implication on China Banking Reform - Lin, Zhuoxi (2011)
The China banking reform started in 1987, for years it is processed in a view of improving efficiency and resource allocation. The most recent reform have been carried out to focus on the joint stock reform related to privatisation and listing of bank shares, liberalisation of business to the foreign banks, encouraging diversifications into intermediary business beyond the traditional deposit and loan activities, and the consolidation reform of the city and rural commercial banks. Meanwhile, the structure change of the China banking sector, and the most recent global financial crisis, all have impact on the China commercial bank performance. We collect a sample of 108 commercial banks from the period 2003 to 2010, and investigate the effect of the determinants on bank performance. To assess whether these objectives have been achieved, this study further investigate how well different types of banks have performed during the sample period. Potential determinants at bank specific level, industry level, and macroeconomic level are examined in the panel data models. We have adopted two dependent variables in our model, which return on average asset (ROAA) as proxy for bank overall performance, and net interest margin (NIM) to detect the traditional interest income profitability. The empirical result suggests that most of the considered determinants factor have statistically significant impact on China banks profitability, and the impact remain stable across bank types, and also the NIM is better explained by the determinants than the ROAA. Capital adequacy ratio, loan to asset ratio and size effect are found to have positive impact on bank performance, whereas liquidity risk is still found to be problematic, and public listing measure is found to be insignificant. The industry variable concentration is found to bring monopoly profits to the large commercial banks, and the opening up statistically found to improve the domestic commercial bank performance, however the impact on foreign bank performance is failed to investigate due to the short sample time period. Although macroeconomic variables have found to have significant negative effect, banks are able to transfer the macro environment loss to customers.